Copper-catalyzed direct arylation of indoles and related (hetero)arenes: a ligandless and solvent-free approach - Pandey, Dilip K.; Shabade, Anand B.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2020)
A ligandless and solvent-free copper-catalyzed method for the regioselective C-H bond arylation of indoles and related heteroarenes is reported. The use of CuCl efficiently catalyzes the direct coupling of diverse heteroarenes with aryl iodides via chelation-assistance. This reaction could tolerate sensitive and structurally diverse functionalities, including halides, ethers, thioethers, amines, indolyl, pyrrolyl and carbazolyl groups. The directing group, 2-pyridinyl can be smoothly removed to generate C-2 arylated free-NH indoles, and the arylated indoles can further be functionalized into Tryptamine derivatives. Preliminary mechanistic study revealed a radical pathway for the arylation reaction.
Keywords: Arylation; C-H activation; Chelation-assistance; Copper; Indole; Solvent-free